2018
DOI: 10.1073/pnas.1801025115
|View full text |Cite
|
Sign up to set email alerts
|

Ligand metathesis as rational strategy for the synthesis of cubane-type heteroleptic iron–sulfur clusters relevant to the FeMo cofactor

Abstract: Molybdenum-dependent nitrogenases catalyze the transformation of dinitrogen into ammonia under ambient conditions. The active site (FeMo cofactor) is the structurally and electronically complex weak-field metal cluster [MoFeSC] built of FeS and MoFeSC portions connected by three sulfur bridges and containing an interstitial carbon atom centered in an Fe trigonal prism. Chemical synthesis of this cluster is a major challenge in biomimetic inorganic chemistry. One synthetic approach of core ligand metathesis has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 18 publications
4
44
0
Order By: Relevance
“…In the single-crystal structures as evident in Figure 1, cluster anions 3a, b exhibit analogous centrosymmetric structures.T he cluster is constituted by connection of ap air of cubane-type subunit via two Fe-N edges in head-to-tail mode to form aFe 2 N 2 rhomb,inwhich both nitride ligands adopt m 4bridging mode.Within the rhomb of 3a,the intra-cubane Fe À Nb ond length on the bridging edge at 1.966 (5) is longer than the other two intra-cubane Fe-N contacts of 1.901(5) and 1.888(5) ,a sw ell as the inter-cubane Fe3-N1 i distance at 1.881 (5) .T he molecule also holds quasi-mirror symmetry upon the plane of Fe3-N1-Fe3 i -N1 i .T he average Fe À Nb ond length within the cubic subunit is 1.918(5) ,b eing slightly shorter than that of 1.936(3) in the reported imide bridged cubane cluster. [49] Theb ond length pattern is indicative of tight binding between subunits and Fe-N distances in this cluster are comparable with those for reported iron-nitride complexes with FeÀNs ingle bond [16,[42][43][44][45] (See Table S2 for alist of FeÀNb onds in selected iron nitride complexes).…”
supporting
confidence: 86%
“…In the single-crystal structures as evident in Figure 1, cluster anions 3a, b exhibit analogous centrosymmetric structures.T he cluster is constituted by connection of ap air of cubane-type subunit via two Fe-N edges in head-to-tail mode to form aFe 2 N 2 rhomb,inwhich both nitride ligands adopt m 4bridging mode.Within the rhomb of 3a,the intra-cubane Fe À Nb ond length on the bridging edge at 1.966 (5) is longer than the other two intra-cubane Fe-N contacts of 1.901(5) and 1.888(5) ,a sw ell as the inter-cubane Fe3-N1 i distance at 1.881 (5) .T he molecule also holds quasi-mirror symmetry upon the plane of Fe3-N1-Fe3 i -N1 i .T he average Fe À Nb ond length within the cubic subunit is 1.918(5) ,b eing slightly shorter than that of 1.936(3) in the reported imide bridged cubane cluster. [49] Theb ond length pattern is indicative of tight binding between subunits and Fe-N distances in this cluster are comparable with those for reported iron-nitride complexes with FeÀNs ingle bond [16,[42][43][44][45] (See Table S2 for alist of FeÀNb onds in selected iron nitride complexes).…”
supporting
confidence: 86%
“…The molecule also holds quasi‐mirror symmetry upon the plane of Fe3‐N1‐Fe3 i ‐N1 i . The average Fe−N bond length within the cubic subunit is 1.918(5) Å, being slightly shorter than that of 1.936(3) Å in the reported imide bridged cubane cluster . The bond length pattern is indicative of tight binding between subunits and Fe–N distances in this cluster are comparable with those for reported iron‐nitride complexes with Fe−N single bond (See Table S2 for a list of Fe−N bonds in selected iron nitride complexes).…”
Section: Methodssupporting
confidence: 69%
“…Embedding a carbon donor into analogues of the FeMo-co as an interstitial carbon for mimicking the biological nitrogenase is especially challenging. Xu et al [117] reported that a core halide ligand (Cl − or Br − ) replacing thiolate was incorporated into a binding site of the heterometallic clusters using one-electron reductant sodium benzophenone ketyl. The new approach provided opportunities to synthesize the analogues more similar to FeMo-co, because core halides are easily replaced with carbon ligands through metathesis reactions.…”
Section: Incorporating Carbon Atoms Into Femo-co Analoguesmentioning
confidence: 99%